БОШЛАНҒИЧ СИНФ ЎҚУВЧИЛАРИНИНГ ЭСТЕТИК ТАРБИЯСИНИ ШАКЛЛАНТИРИШ - Куттибекова, Г.Т. (SCIENCE and SOCIETY, 2019)
Education of the highly-develop young generation is one of the actual issues today. Today for the acception of much information stream every one should possess appropriate knowledge, skills and qualification. Taking into account this fact, it’s necessary to develop these qualities in children since their earlier age.